BILATERAL TRANSABDOMINAL PREPERITONEAL HERNIA REPAIR IN PATIENTS WITH PRIMARY UNILATERAL INGUINAL HERNIA - Huseynov, S.E.; Muslumov, G.F.; Ahmedov, F.T. (World of Medicine and Biology, 2025)
In this article, we used the advantages of laparoscopic surgery to determine the safety and efficacy of prophylactic bilateral transabdominal preperitoneal repair surgery performed on the contralateral side in unilateral inguinal hernias. We performed such operations on 101 patients with primary unilateral inguinal hernias. The patients were divided into two groups: 49 patients underwent unilateral transabdominal preperitoneal repair and 52 patients prophylactic bilateral transabdominal preperitoneal repair. The results were compared in the short and long term (3 years). In bilateral transabdominal preperitoneal repair group, the average operating time was 24 minutes longer, and there were no significant differences in other parameters and postoperative indicators such as postop pain, length of stay, chronic pain, seroma hematoma, and recurrences.
Keywords: inguinal hernia; bilateral TAPP; prophylactic repair; chronic pain; recurrence